'if he chooses to speak from these roots': entanglement and uncertainty in Charles Olson's quantum ecopoetics. Issue 4 (2nd October 2019) - Daw, Sarah
ABSTRACT: This article offers a material ecocritical reading of the work of Charles Olson, arguing that Olson's oeuvre constitutes a critical moment in the evolution of contemporary ecological thought. The article begins by highlighting the revival of interest in mid-twentieth-century philosophy of physics texts within 'new materialism', before moving into a comprehensive exploration of the degree to which the same mid-century science writing transformed Olson's literary depictions of the human and the environment. This work exposes the significant parallels between Olson's literary response to quantum ideas and their deployment in contemporary theory, providing valuable historical context to ecocriticism's current 'new materialist' turn.